Propuesta de Gestión para el Desarrollo Turístico de la parroquia Urdaneta, cantón Saraguro - Montaño Ramón, Dayana Gabriela (2025)
Sustainable tourism is focused on meeting current needs without affecting the capacity for future progress. It seeks a transparent development that enhances quality of life while respecting the environment, cultural heritage, and life. This approach fosters a tourism culture among both the community and visitors, actively involving them in sustainable activities that contribute to the tourism development of a certain community. Urdaneta is a large parish with significant cultural and natural diversity, requiring a strategic direction that leads to its adequate sustainable development. Therefore, the general objective of this project is to develop a management proposal for the tourist development of the Urdaneta Parish, supported by three specific objectives: analyzing the current situation of tourism reality in Urdaneta, identifying proposals aimed at the tourist development of Urdaneta, and finally proposing tourist development strategies for Urdaneta Parish in Saraguro Canton. The methodology employed integrates both qualitative and quantitative approaches to achieve the stated objectives. Likewise, a total of 302 surveys were conducted to measure the profile of tourist demand, 151 in Loja Canton and 151 in Cuenca Canton. On the other hand, 253 surveys were conducted within the parish, which also consisted of some questions to gauge the community’s perception of tourism development. Consequently, the 2021-2025 Opportunity Creation Plan was used as a support guide to consider proposals and strategies focused on environmental, economic, and sociocultural fields. In conclusion, Urdaneta parish has certain bases for tourism; it is not exploited, nor is it on track to develop sustainably, which delays its future growth.